1998
DOI: 10.1023/a:1005701116297
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of DMBA-induced mammary gland carcinogenesis – preventive effects of free oxygen radical scavengers

Abstract: This study was carried out to determine the effects of Mangan-Desferrioxamine (Mn-DFX) and Verapamil (VRP) in 7,12-dimethyl-benz-[a]anthracene (DMBA) induced mammary carcinoma. 70 Spraque Dawley rats were divided into four groups; as DMBA alone, DMBA + Mn-DFX, DMBA + VRP, and control. Incidence, multiplicity, and size of tumors were evaluated in addition to analyses of DNA ploidy status and proliferation index by flow cytometric technique. The results revealed that Mn-DFX and VRP caused significant decreases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…However, a critical analysis of data on the treatment of hypertension with these drugs allowed WHO experts to conclude that such information was unreasonable [19][20]. In addition, it was shown that with the introduction of certain carcinogens (7, 12-dimethylbenzantracene) into animals, verapamil suppressed the development of tumors in rats [21]. Other researchers have shown the absence of tumor-stimulating activity of verapamil during prolonged exposure in rats [22].…”
Section: Figure 2 the Ratio Of Blood Cells Aggregation Indicators Unmentioning
confidence: 99%
“…However, a critical analysis of data on the treatment of hypertension with these drugs allowed WHO experts to conclude that such information was unreasonable [19][20]. In addition, it was shown that with the introduction of certain carcinogens (7, 12-dimethylbenzantracene) into animals, verapamil suppressed the development of tumors in rats [21]. Other researchers have shown the absence of tumor-stimulating activity of verapamil during prolonged exposure in rats [22].…”
Section: Figure 2 the Ratio Of Blood Cells Aggregation Indicators Unmentioning
confidence: 99%
“…Однако критический анализ данных о лечении гипертонической болезни этими препаратами позволил экспертам ВОЗ сделать заключение о необоснованности таких сведений [17,18]. Кроме того, показано, что при введении в организм животных некоторых канцерогенов (7,12-диметилбензантрацен) верапамил подавлял возникновение опухолей у крыс [19]. Другими исследователями показано отсутствие опухольстимулирующей активности верапамила при длительных воздействиях на крысах [20].…”
Section: Ukrainian Neurosurgical Journal Vol 25 N3 2019unclassified